The Hippo-YAP pathway in various cardiovascular diseases: Focusing on the inflammatory response - Ancheng Zheng; Qishan Chen; Li Zhang (Frontiers in Immunology, 2022)
The Hippo pathway was initially discovered in Drosophila melanogaster and mammals as a key regulator of tissue growth both in physiological and pathological states. Numerous studies depict the vital role of the Hippo pathway in cardiovascular development, heart regeneration, organ size and vascular remodeling through the regulation of YAP (yes-associated protein) translocation. Recently, an increasing number of studies have focused on the Hippo-YAP pathway in inflammation and immunology. Although the Hippo-YAP pathway has been revealed to play controversial roles in different contexts and cell types in the cardiovascular system, the mechanisms regulating tissue inflammation and the immune response remain to be clarified. In this review, we summarize findings from the past decade on the function and mechanism of the Hippo-YAP pathway in CVDs (cardiovascular diseases) such as myocardial infarction, cardiomyopathy and atherosclerosis. In particular, we emphasize the role of the Hippo-YAP pathway in regulating inflammatory cell infiltration and inflammatory cytokine activation.